Psychological Assistance in Enhancing the Emotional Intelligence of Tahfidz Students at Rumah El Imam Ibnu Qoyyim, Yayasan Tarbiyatul Ajyal Darussalam - Amaliyah, Rizki; Annisa, Vania Syifa (Yayasan Rumah Ilmu Professor, 2025)
Implementation of psychological mentoring program in improving emotional intelligence of tahfidz students at Rumah Qur'an El-Imam Ibnu Qoyyim, Tarbiyatul Ajyal Darussalam Foundation. Mentoring is carried out through psychoeducation, spiritual guidance, and daily worship habits integrated into students' activities. The results of the internship show that a psychological approach combined with spiritual strengthening is effective in helping students recognize, manage, and express emotions in a healthy way. In addition, this program also plays a role in reducing psychological stress due to the burden of memorization and social dynamics in the Islamic boarding school environment. The involvement of musyrifah who are emotionally and morally ready also supports the adaptation process and character development of students. Overall, psychological mentoring has been proven to improve mental well-being, learning motivation, and shape the character of students who are independent and have noble morals.